Coupled electrophysiological, hemodynamic, and cerebrospinal fluid oscillations in human sleep - Fultz, Nina E.; Bonmassar, Giorgio; Setsompop, Kawin; Stickgold, Robert A.; Rosen, Bruce R.; Polimeni, Jonathan R.; Lewis, Laura D. (Science (American Association for the Advancement of Science), 2019)
Sleep is essential for both cognition and maintenance of healthy brain function. Slow waves in neural activity contribute to memory consolidation, whereas cerebrospinal fluid (CSF) clears metabolic waste products from the brain. Whether these two processes are related is not known. We used accelerated neuroimaging to measure physiological and neural dynamics in the human brain. We discovered a coherent pattern of oscillating electrophysiological, hemodynamic, and CSF dynamics that appears during non–rapid eye movement sleep. Neural slow waves are followed by hemodynamic oscillations, which in turn are coupled to CSF flow. These results demonstrate that the sleeping brain exhibits waves of CSF flow on a macroscopic scale, and these CSF dynamics are interlinked with neural and hemodynamic rhythms.